Turner's syndrome presenting as metabolic bone disease - Kamalanathan, Sadishkumar (Medknow Publications & Media Pvt Ltd, 2012)
Turner's syndrome is a genetic disorder with a complete or partial absence of one X chromosome with characteristic phenotypic features. The prevalence of renal anomalies in turner syndrome is 30–40%. However, the renal function is usually normal. We report a case of Turner's syndrome presenting with chronic kidney disease and renal osteodystrophy.